Chapter The Presence of Absence. Longing and Nostalgia in Post-Soviet Art and Literature - Marchesini, Irina (Biblioteca di Studi Slavistici, 2015)
This article explores the phenomenon of nostalgia for the Soviet era found in contemporary Russian society and manifested both in contemporary art, such as in the installations of Il'ja Kabakov, Sergej Volkov, and Jevgenij Fiks, and in modern literature, especially in the prose of Andrej Astvacaturov. Such regret for a bygone past primarily mourns not the apparatus of the Soviet state, but the routine and the quality of familiar daily life. Insights from the fields of visual studies and trauma studies undergird this exploration of the relationship between a work of art's visual composition and its representation of toska, memory, and material culture in the Soviet era. By juxtaposing artwork with literary prose, we reveal the significant role had by 'reflective' toska-nostalgia (as defined by Svetlana Boym, 2001) in the formation of post-Soviet identity.